Determining the Analysis of the Stability of Embankments against Sliding and Prediction of Sliding and Critical Factor of Safety - Salmasi , Farzin; Abraham, John; Nourani, Bahram (Novel Perspectives of Engineering Research Vol. 9, 2022)
Slope stability refers to the ability of inclined soil or rock slopes to withstand or undergo movement. The stability of slopes is a subject of study in soil mechanics, geotechnical engineering and engineering geology. Analyses are generally aimed at understanding the causes of slope failure, or the factors that can potentially trigger a slope movement, resulting in a landslide. Analyses also are aimed at preventing the initiation of movement, slowing it down or arresting it through mitigation countermeasures. Different factors affect the stability of slopes. These parameters include soil cohesion, soil friction angle, existing stresses and water surface level. These parameters influence the shear resistance of the slip surface. The limit equilibrium method (LEM) is one of the oldest methods for determining the critical slip surface and minimum factor of safety. In this paper, the effects of soil material parameters including soil specific weight ( \(γ\) ), cohesion (C), angle of internal friction ( \(φ\)), geometric parameters of slope including angle with the horizontal ( \(β\) ), and slope height (H) on factor of safety (Fs) are investigated. Fs is considered in two scenarios: (i) a slope with dry conditions, and (ii) with a steady-state saturated condition that comprises water level drawdown circumstances. In addition, a slip circle is also investigated. For these calculations, the SLOPE/W software, part of the Geo-Studio software suite, is implemented. The findings demonstrate that lowering the water table level and removing the hydrostatic pressure on the slope reduces the safety factor. When the plane and circular failure surfaces were compared, the plane failure method produced good results only for near-vertical slopes. Results also show that for \(β\) < \(60^{°}\) each of the three types of slip occurred, but for \(β\) > \(60^{°}\) only toe circle slips occur. Linear and nonlinear regression equations were obtained for estimating slope safety factor.